Two-way migration between similiar countries - Udo Kreickemeier; Jens Wrona (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2015)
We develop a model to explain two-way migration of high-skilled individuals between countries that are similar in their economic characteristics. High-skilled migration results from the combination of workers whose abilities are private knowledge, and a production technology that gives incentives to firms for hiring workers of similar ability. In the presence of migration cost, high-skilled workers self-select into the group of migrants. The laissez-faire equilibrium features too much migration, explained by a negative migration externality. We also show that for sufficiently low levels of migration cost the optimal level of migration, while smaller than in the laissez-faire equilibrium, is strictly positive. Finally, we extend our model into different directions to capture stylized facts in the data and show that our baseline results also hold in these more complex modelling environments.
Keywords: D82; F22; 330; International Migration; Skilled Workers; Positive Assortative Matching